Tort law : a modern perspective - Hylton, Keith N. (New York : Cambridge University Press, 2016)
Tort Law: A Modern Perspective is an advanced yet accessible introduction to tort law for lawyers, law students, and others. Reflecting the way tort law is taught today, it explains the cases and legal doctrines commonly found in casebooks using modern ideas about public policy, economics, and philosophy. With an emphasis on policy rationales, Tort Law encourages readers to think critically about the justifications for legal doctrines. Although the topic of torts is specific, the conceptual approach should pay dividends to those who are interested broadly in regulatory policy and the role of law. Incorporating three decades of advancements in tort scholarship, Tort Law is the textbook for modern torts classrooms.
Policy and tort law -- Evolution of tort law -- Intentional torts -- Theoretical foundations of strict liability -- The reasonable person -- Customs, statutes, and the reasonable person -- Inferring negligence -- Contributory negligence and assumption of risk -- Contributory negligence, comparative negligence, and incentives for care -- Joint and several liability, and vicarious liability -- Factual causation -- Proximate cause -- Duty to rescue and special relationships -- Strict liability : conversion, abnormally dangerous activities, and nuisance -- Defamation -- Products liability -- Damages.
Title from publisher's bibliographic system (viewed on 06 Jun 2016).
Keywords: Torts -- United States